Insurance as a risk transfer mechanism in Small and Medium Enterprises (SMEs) - Md. Jadi, Diara; Abdul Manab, Norlida; Ahmad, Shahrul Nizam (2014)
This paper aims to provide an insight into the application of insurance as a risk transfer mechanism surrounding the small and medium enterprises (SMEs).SMEs owners must develop a sound risk management program and utilize appropriate risk transfer mechanism in order to protect their business and enhance their opportunity for business sustainability.Insurance is a useful tool for managing risks.Even though it is not the ultimate solution in a risk management strategy, it is indeed an important aspect in any business operations in order to protect assets and to reduce losses.However, the practice is slightly distorted.SMEs businesses in various countries are facing issues such as lack of good risk management strategy, inadequate insurance protection, non-insurance, non-compliance and lack of awareness on this matter.This paper could be beneficial to the SMEs by increasing their awareness about the significance of insurance as a risk transfer mechanism, types of insurance schemes available in the market and the impact of good risk management practices